2018
DOI: 10.1371/journal.pone.0197753
|View full text |Cite
|
Sign up to set email alerts
|

Oyster aquaculture impacts Zostera marina epibiont community composition in Akkeshi-ko estuary, Japan

Abstract: Coastal fisheries are in decline worldwide, and aquaculture has become an increasingly popular way to meet seafood demand. While finfish aquaculture can have substantial adverse effects on coastal ecosystems due mostly to necessary feed inputs, bivalves graze on natural phytoplankton and are often considered for their positive ecosystem services. We conducted two independent studies to investigate the effects of long-line Crassostrea gigas oyster aquaculture on Zostera marina seagrass beds and associated epibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In Akkeshi Lake, Hokkaido, Smith et al (2018) found that the cultured oysters fed on epiphytic diatoms and epiphyte propagules before they settled on seagrass, which reduced epiphyte loads and influenced subsequent faunal settlements. As a result, the presence of cultured oysters might indirectly affect seagrass by changing the composition and relative abundance of species such as sessile polychaetes, gastropods, and amphipods.…”
Section: Discussionmentioning
confidence: 99%
“…In Akkeshi Lake, Hokkaido, Smith et al (2018) found that the cultured oysters fed on epiphytic diatoms and epiphyte propagules before they settled on seagrass, which reduced epiphyte loads and influenced subsequent faunal settlements. As a result, the presence of cultured oysters might indirectly affect seagrass by changing the composition and relative abundance of species such as sessile polychaetes, gastropods, and amphipods.…”
Section: Discussionmentioning
confidence: 99%
“…There are 30 recorded extant Osteridae species in Asia, including 11 species of Crassostrea . Although most known natural oyster populations are reported to be over‐harvested and have since been maintained by aquaculture in Asia, Crassostrea species have been reported to form natural beds and reefs along Asian intertidal shorelines, including northern China (Quan et al 2012), Thailand (Brohmanonda et al 1988), and Japan (Smith et al 2018). Given their wide range of distribution and high diversity within Asia, they have the potential to provide ecosystem services that are valuable to the health and sustainability of coastal waters.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics shown relate only to such communities, but these can be vitally important for understanding general ecological theory (Connell ). Particularly when small calcareous domiciles are counted as components of larger species assemblages, domicile abundances are commonly reported without information on whether any were dead and what the proportion may be (Clark et al , McGowan and Iyengar , KrzemiƄska and Kuklinski , Smith et al , Traiger and Konar , among other recent examples). The diagram shows the ecological processes (R = recruitment, M = mortality, T = taphonomic degradation) that may be considered to cause a hypothetical distributional pattern of differing density of domicile structures, depending on whether information is known about the status of occupancy.…”
Section: Introductionmentioning
confidence: 99%